Forwards-Backwards: Internal Party Democracy in Irish Political Parties - Reidy, Theresa (Frontiers in Political Science, 2022)
All political parties want candidates that will win elections but electability is an elusive trait and how it is understood, and pursued varies greatly. Political parties have formal rules, and informal practices and preferences, for selecting candidates and these tend to be dynamic, changing from election to election as parties review their performance and respond to changes in the political and legal environment. Generally, the last thirty years has witnessed a drift toward greater internal party democracy as party members have been given more extensive roles in important decisions such as selecting candidates for election. Ireland is an interesting case study that on the surface embraced internal party democracy (IPD) at an early point. All the major parties have empowered party members to vote for candidates at district level selection conventions. But closer inspection reveals that decision making remains highly qualified with party elites retaining decisive influence over the criteria which structure decisions by party members. Multi-seat constituencies, party finance rules and more recently the introduction of a legally binding gender quota mean that internal party democracy is far more constrained than the widespread adoption of one member, one vote and constituency level selection conventions might suggest. However, even the modest changes in the power balance in selection has contributed to an evolving profile of candidates at Irish general elections.